1978
DOI: 10.1111/j.1365-2621.1978.tb15287.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of Chalkiness in Soymilk

Abstract: Chalkiness is a defect used to describe a food which coats the mouth and throat with fine, grainy particles. This study evaluates the processing and formulation variables which affect chalkiness of Illinois process soymilk produced from dehulled soybeans. Alkalinity of the blanch solution, homogenization conditions, soymilk pH, and solids concentration had the most pronounced effects on chalkiness. Increasing blanch alkalinity decreased chalkiness; beverages adjusted to higher final pH were less chalky. Homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 1 publication
2
39
0
1
Order By: Relevance
“…The seeds of some plants, such as peanuts, soybeans and pine nuts, they contain high oil content and abundant protein. The technology of aqueous extracts has been used to prepare milk-like beverages (Kuntz, Nelson, Steinberg, & Wei, 1978;Lee & Rhee, 2003;Lee & Beuchat, 1992;Nelson, Steinberg, & Wei, 1976;Wilkens, Mattick, & Hand, 1967). Nowadays enzymes are used to ensure optimal ginkgo juice yield and quality because ginkgo juice processing using mechanical pressing of the kernel results in poor juice yield and instability.…”
Section: Introductionmentioning
confidence: 98%
“…The seeds of some plants, such as peanuts, soybeans and pine nuts, they contain high oil content and abundant protein. The technology of aqueous extracts has been used to prepare milk-like beverages (Kuntz, Nelson, Steinberg, & Wei, 1978;Lee & Rhee, 2003;Lee & Beuchat, 1992;Nelson, Steinberg, & Wei, 1976;Wilkens, Mattick, & Hand, 1967). Nowadays enzymes are used to ensure optimal ginkgo juice yield and quality because ginkgo juice processing using mechanical pressing of the kernel results in poor juice yield and instability.…”
Section: Introductionmentioning
confidence: 98%
“…Smith et al (1961) reported that proteins and insoluble carbohydrates were the primary soybean components responsible for absorption of water, and the sludge from the water extraction containing 65% water-insoluble carbohydrate held more than five times more water than the extracted protein. Kuntz et al (1978) and Urbanski et al (1982) also demonstrated the high water uptake of ISB sludge. However, as the sludge content increased the overrun decreased; this was probably due to the extra solids to be carried by the foam and the exponential increase or viscosity with increasing sludge (Urbanski et al, 1982).…”
Section: Effect Of Soybean Components On Whipped Topping Performancementioning
confidence: 89%
“…We attributed the increase in stability to partial thermal denaturation of peanut proteins. Similarly, heat treatment increased the stability of emulsions (Kinsella & Whitehead, 1988;Das & Kinsella, 1990) and soybean beverage (Kuntz et al, 1978;Priepke et al, 1980). The more readily a protein molecule can unfold at the oil/water interface, the higher is its emulsification capacity.…”
Section: Emulsion Stabilitymentioning
confidence: 95%